Biosorption of rare earth elements using biomass of Sargassum on El-Atshan Trachytic sill, Central Eastern Desert, Egypt - Nora Shenouda Gad (Egyptian Journal of Petroleum)
The use of unicellular brown micro-algae has several advantages over conventional methods for removing rare earth elements (REEs) from lithogenic materials. A comparative study is made to investigate the uptake and bioaccumulation of REEs from trachytic samples collected from El-Atshan mine area in the Central Eastern Desert of Egypt. The examined samples are characterized by their high REE content. Using Sargassum algae; it appears possible to reduce the abundance of the Light Rare Earths (LREEs; La, Ce, Nd, Pm, Sm and Eu) that have a large atomic number. However, higher efficiency of the separation has been recorded for the heavy rare earths (HREEs) which display a marked control of quantum failing (tetrad effect).